25.1: Invited Paper: Quantum dots based full‐color display on micro‐light‐emitting‐diode technology. (28th November 2018) - LIN, CHIH-HAO; LEE, CHUN-FU; LIN, CHIEN-CHUNG; CHU, CHEN-HSIEN; SHER, CHIN-WEI; LIU, ZHAO-JUN; KUO, HAO-CHUNG
Abstract : In this study, we would like to demonstrate a quantum‐dot (QD)‐based full‐color emission red‐green‐blue (RGB) micro‐light‐emitting‐diode (micro‐LED) array with the reduced optical cross‐talk effect by a photoresist mold method. The UV micro‐LED array is used as an efficient excitation source for the QDs. The aerosol jet technique provides a narrow linewidth on the micrometer scale for a precise jet of QDs on the micro‐LEDs. In order to reduce the optical cross‐talk effect, a simple lithography method and photoresist are used to fabricate the mold, which consists of a window for QD jetting and a blocking wall for cross‐talk reduction. The cross‐talk effect of the well‐confined QDs in the window is confirmed by a fluorescence microscope, which shows clear independence QD pixels. A distributed Bragg reflector is covered on the micro‐LED array and the QDs' jetted mold to further increase the reuse of UV light. The enhanced light emission of the QDs is 5%, 32%, and 23% for blue, green, and red QDs, respectively.